VIRTUAL REALITY: SEBUAH MODALITAS PELENGKAP EDUKASI ANATOMI - Sasongko, Bagas Ekasangga; Harahap, Ida Lestari; Herlina, Lenny (Poltekkes Kemenkes Mataram, 2023)
Anatomi menjadi landasan dasar ilmu-ilmu kedokteran sehingga pentingnya mempelajari anatomi untuk menunjang praktik klinik di masa depan, baik dalam pemeriksaan dan diagnosis pasien, maupun komunikasi antar sesama profesi kesehatan. Anatomi dapat dipelajari dengan modalitas dua dimensi dan utamanya dengan modalitas tiga dimensi. Kadaver menjadi modalitas tiga dimensi yang telah digunakan selama berabad-abad lamanya. Kadaver mampu menghadirkan pemahaman spasial yang baik dan mendalam mengenai struktur tubuh manusia, serta memberikan sensasi sentuhan yang tidak bisa didapatkan oleh modalitas pembelajaran lainnya. Dengan bertambahnya institusi pendidikan kedokteran serta permasalahan berkaitan dengan kesehatan, agama, etika, medikolegal, waktu dan biaya, menjadikan kadaver semakin langka untuk didapatkan. Hal ini mengharuskan mahasiswa menambah pemahaman mereka dengan modalitas lain yang banyaknya berbentuk dua dimensi. Modalitas dua dimensi pun memiliki kelemahan yang hanya bisa didapatkan dari modalitas tiga dimensi sehingga tetap diperlukan modalitas tiga dimensi lainnya selain kadaver. Virtual Reality hadir menjadi alternatif modalitas pelengkap yang efektif dalam membantu pemahaman dalam mempelajari anatomi. Artikel ini disusun dengan pencarian literatur digital pada online database yang tersedia berupa artikel penelitian dan tinjauan pustaka. Pencarian literatur menghasilkan rangkaian pembahasan mengenai pembelajaran anatomi, peran kadaver dalam pembelajaran anatomi, dan virtual reality sebagai alternatif modalitas tiga dimensi. Kesimpulan pada artikel ini, yaitu virtual reality dengan kelebihan dan kekurangannya mampu menjadi pelengkap pada pembelajaran anatomi, meskipun tidak dapat menggantikan peran kadaver seutuhnya.AbstractAnatomy is the basic foundation of medical sciences so it is important to study anatomy to support clinical practice in the future, both in the examination and diagnosis of patients, as well as in communication between fellow health professionals. Anatomy can be studied with two-dimensional modalities and mainly with three-dimensional modalities. Cadaver became a three-dimensional modality that has been used for centuries. Cadavers can present a good and deep spatial understanding of the structure of the human body, as well as provide tactile sensations that other learning modalities cannot get. With the increase in medical education institutions and problems related to health, religion, ethics, medicolegal, time, and cost, cadavers are increasingly rare to obtain. This requires students to increase their understanding of other modalities that are mostly two dimensions. The two-dimensional modalities also have a weakness that can only be obtained from the two-dimensional modalities so other two-dimensional modalities besides cadavers are still needed. Virtual Reality is here to be an effective alternative complementary modality in helping understanding in studying anatomy. This article is compiled by searching digital literature on the online database available in the form of research articles and literature reviews. A literature search resulted in a series of discussions on anatomical learning, the role of cadavers in anatomical learning, and virtual reality as an alternative to three-dimensional modalities. The conclusion of this article is that virtual reality with its advantages and disadvantages can be a complement to the learning of anatomy, although it cannot replace the role of cadavers completely.Â AbstractAnatomy is the basic foundation of medical sciences so it is important to study anatomy to support clinical practice in the future, both in the examination and diagnosis of patients, as well as in communication between fellow health professionals. Anatomy can be studied with two-dimensional modalities and mainly with three-dimensional modalities. Cadaver became a three-dimensional modality that has been used for centuries. Cadavers can present a good and deep spatial understanding of the structure of the human body, as well as provide tactile sensations that other learning modalities cannot get. With the increase in medical education institutions and problems related to health, religion, ethics, medicolegal, time, and cost, cadavers are increasingly rare to obtain. This requires students to increase their understanding of other modalities that are mostly two dimensions. The two-dimensional modalities also have a weakness that can only be obtained from the two-dimensional modalities so other two-dimensional modalities besides cadavers are still needed. Virtual Reality is here to be an effective alternative complementary modality in helping understanding in studying anatomy. This article is compiled by searching digital literature on the online database available in the form of research articles and literature reviews. A literature search resulted in a series of discussions on anatomical learning, the role of cadavers in anatomical learning, and virtual reality as an alternative to three-dimensional modalities. The conclusion of this article is that virtual reality with its advantages and disadvantages can be a complement to the learning of anatomy, although it cannot replace the role of cadavers completely.